RELEVANCE OF INFORMATION WARFARE MODELS TO CRITICAL INFRASTRUCTURE PROTECTION - Van Niekerk, Brett; Maharaj, Manoj S. (Scientia Militaria - South African Journal of Military Studies, 2011)
This article illustrates the relevance of information warfare models to critical infrastructure protection. Analogies of information warfare models to those of information security and information systems were used to deconstruct the models into their fundamental components and this will be discussed. The models were applied to critical infrastructures to illustrate the relevance to critical infrastructure protection. By considering the interdependencies of the critical infrastructure sectors, it will be shown how all critical infrastructures can be modelled as information infrastructures when considering information warfare attacks.